2022
DOI: 10.1038/s41598-022-19846-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorella extracts on growth of Capsicum annuum L. seedlings

Abstract: The long-term application of chemical fertilizers has caused to the farmland soil compaction, water pollution, and reduced the quality of vegetable to some extent. So, its become a trend in agriculture to find new bio-fertilizers. Chlorella extract is rich in amino acids, peptides, nucleic acids, growth hormones, potassium, calcium, magnesium, iron, zinc ions, vitamin E, B1, B2, C, B6, folic acid, free biotin and chlorophyll. Chlorella extract can promote biological growth, mainly by stimulating the speed of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Furthermore, the total content of phenolics, avonoids, and glucosinolates in broccoli were increased by the additional application of organic fertilizers [51]. Chlorella extracts have been shown to promote plant growth in pepper (Capsicum annuum) plants [52]. For example, plant height, leaf area, and fruit and shoot weights of pepper plants were increased after supplying Chlorella extracts for 21 days compared to the control.…”
Section: Soil Microbial Compositionmentioning
confidence: 99%
“…Furthermore, the total content of phenolics, avonoids, and glucosinolates in broccoli were increased by the additional application of organic fertilizers [51]. Chlorella extracts have been shown to promote plant growth in pepper (Capsicum annuum) plants [52]. For example, plant height, leaf area, and fruit and shoot weights of pepper plants were increased after supplying Chlorella extracts for 21 days compared to the control.…”
Section: Soil Microbial Compositionmentioning
confidence: 99%
“…Additionally, recent work has demonstrated that microalgae are important members of the plant microbiome and may greatly impact plant growth, development, and stress resistance [ 11 ]. Several reports have demonstrated that not only cyanobacteria, but also eukaryotic microalgae such as members of the Chlorellaceae family are able to promote the growth of several crop plants (e.g., tomato, wheat, soybean, pepper) [ 12 , 13 , 14 , 15 ], and this is accomplished using microalgae cell cultures or extracts and diverse plant inoculation strategies (e.g., foliar or soil application) [ 11 ]. Chlorella cell-free supernatants can also reduce the onset of shoot and flower senescence with potential benefits for increasing flower shelf-life [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Sh.L. Tian et al (2022), the effect of Chlorella vulgaris Beijer extract on the growth of Capsicum annuum plants of the "Chao Tian Jiao" variety was investigated. Two weeks after transplanting into pots, the seedlings of the experimental groups were sprayed with Chlorella extracts.…”
Section: Introductionmentioning
confidence: 99%